AI DAN BUDAYA LOKAL DALAM PRAKTIK HR: STUDI KASUS HUMANISASI TEKNOLOGI DALAM LINGKUP ORGANISASI DI MANGGARAI - Lery, Yohana Cintami; Jangku, Wilhelmus Sabatani (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to understand the dynamics of the application of artificial intelligence (AI) technology in human resource management (HR) practices in organizations operating in the Manggarai region, which has a strong local cultural background. In this context, cultural values such as kinship, mutual cooperation, and verbal communication still dominate work patterns. A qualitative approach was used with a case study design. Data were collected through in-depth interviews, observations, and document studies, then analyzed thematically. The results of the study reveal four themes as conclusions: (1) the ambiguity of the role of technology in traditional work environments; (2) the humanization of technology as a bridge between local values and modernity; (3) the transformation of work culture from verbal communication to digital systems; and (4) the tension between technological efficiency and socio-psychological well-being